Single-cell RNA transcriptomics reveals differences in the immune status of alcoholic and hepatitis B virus-related liver cirrhosis - Zhang, Pengpeng; Li, Hao; Peng, Bo; Zhang, Yu; Liu, Kai; Cheng, Ke; Ming, Yingzi (Frontiers in Endocrinology, 2023)
Background: Alcoholic and hepatitis B virus (HBV)-related liver cirrhosis has placed a tremendous burden on the healthcare system with limited treatment options. This study explored the differences in the immune status of alcoholic and HBV-related liver cirrhosis. Methods: A total of 15 human liver samples from the Third Xiangya Hospital of Central South University, including five healthy controls (HC group), five alcoholic cirrhosis patients (ALC group), and five HBV-related cirrhosis patients (HBV group) were used. Of these, eight samples, including 3 HC group, 2 ALC group and 3 HBV group, were randomly collected to do single-cell RNA sequencing (scRNA-seq). The degree of steatosis was assessed by H&E staining and the presence of intrahepatic immune cells was evaluated by immunochemistry (IHC). Results: The immune status of alcoholic and HBV-related liver cirrhosis differed significantly. ScRNA-seq analysis identified a higher ratio of intrahepatic monocyte/macrophages and an obvious decreased ratio of T cells and B cells in the ALC group than in the HBV group. IHC staining of intrahepatic monocyte/macrophages, T and B cell exhibited similar results with scRNA-seq analysis. CD5L+ Kupffer cells, a cell type involved in lipid metabolism, were the major monocyte/macrophage subset in ALC liver tissue. H&E staining indicated that the level of steatosis was more severe in the ALC than in the HBV group. Ligand/receptor analysis showed that the T cell exhaustion observed in the ALC liver may be related to the expression of Galectin-9 on Kupffer cells. Fewer B cells were also found in the ALC group and most had higher lipid metabolism, reduced ribosomal activity, and a dysregulated mitochondrial oxidative phosphorylation system. Moreover, scRNA-seq showed a significantly lower ratio of plasma B cells, indicating that the humoral immune response in the ALC liver was similarly dysfunctional. Ligand/receptor analysis also discovered that Galectin-9 expressed on Kupffer cells may inhibit humoral immunity. Conclusion: Patients with ALC have different immune characteristics than those with HBV-induced cirrhosis, including an increased ratio of intrahepatic monocyte/macrophages and a dysfunctional adaptive immune response in the liver. Galectin-9 could serve as a potential therapeutic target for ALC treatment.